(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Hemorrhoid is the anal disease and causes major morbidity and economic burden. Surgical treatment causes major complications. Injection Sclerotherapy is widely used in the treatment of hemorrhoids. So the present study was carried out to find the comparative effectiveness of Injection Sclerotherapy using Polidocanol for the management of second and third degree hemorrhoids. Aims: The aim of the study was to compare the efficacy and safety of polidocanol sclerotherapy in second and third degree hemorrhoids by assessing symptom relief, operative parameters, complications, and treatment outcome at 6 weeks. Materials and Methods: This prospective comparative interventional study was conducted in the Department of General Surgery, Bankura Sammilani Medical College and Hospital over 12 months among 120 patients with second and third degree hemorrhoids who underwent polidocanol injection sclerotherapy and were assessed for treatment outcomes and complications. Results: No significant difference in gender (56.7% vs 53.3%, p = 0.71), but Grade III showed higher prolapse (100% vs 16.7%, p < 0.001), longer injection time (10.5 ± 2.8 vs 8.2 ± 2.1 min, p = 0.002), higher VAS (4.6 ± 1.3 vs 2.8 ± 1.1, p < 0.001), more complications (p < 0.001), and lower complete relief (63.3% vs 86.7%, p < 0.001). Conclusions: Thus injection Sclerotherapy using Polidocanol elicits good results with less complications and low cost. Further, the results have shown that this method is effective in second degree hemorrhoids as that of the third degree hemorrhoids.